The Relationship of Health Literacy with Health status, Preventive Behaviors and Health services Utilization in Baluchistan, Iran - Hossien Izadirad; Iraj Zareban (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Health Literacy has been defined as the cognitive and social skills that determine the motivation and ability of individuals to gain access to, understand and use information in ways which promote and maintain good health. People with inadequate health literacy have poorer health status. Thus, the aim of this study was to determine the status of health literacy and its relationship with general health status, use of health services and preventive behaviors. Materials and Methods: This descriptive-analytical study was conducted on 400 individuals aged 18to 65 years in Balochestan, Iran. Multi-stage cluster sampling was used. Data were collected using Health Literacy for Iranian Adults (HELIA) questionnaires. Data analyses were conducted using Kruskal-Wallis and Mann-Whitney, using SPSS (version 18). Results: The mean age of the studied population was 9.29± 28.7years. Only %32 of adults were found to have adequate health literacy. Inadequate health literacy was more common in older people, ones with fewer years of schooling or lower household income, and females. The health literacy level was associated with outpatient visits, screening, and health status. Individuals with higher levels of health literacy had performed screening more than others. conclusions: Due to the low health literacy level in the target population, educational interventions are needed to develop health literacy skills in the community.